History and progress in rice research and its future perspective in Cambodia - Saito, Kazuki; Pangesti, Nurmi; Flor, Rica Joy; Uch, Chanthol; Laborte, Alice; Khay, Sathya; Orn, Chourn; Kong, Kea; Seng, Vang (Plant production science, 2025)
Since 1993, rice production in Cambodia has increased fivefold, positioning it as a key player in global food security through its export contributions. Considerable expansion of harvested area and its yield improvement have significantly boosted its production and export. Yet, with an average yield of 2.8 t/ha for rainfed lowland and 4.1 t/ha for irrigated lowland, there remains a substantial gap, highlighting the potential for further enhancements in productivity. This study aims to provide the current state of rice cultivation in Cambodia, the challenges it faces, history and progress in rice research, and future research directions focusing on genetic improvement and agronomy. Despite significant advancements, challenges such as climate vulnerability, sub-optimum crop establishment, soil and nutrient, and pest management practices persist, particularly in the dominant rainfed lowland rice systems. Rice varieties, fertilizer management practices, and pest control have been instrumental in addressing some challenges, yet ongoing research is crucial for developing solutions tailored to Cambodia’s unique agricultural landscape. Future efforts must concentrate on developing climate-resilient rice varieties with high market value, sustainable soil and water management practices, and farm diversification options to fortify rice farming against climate change, thereby boosting productivity and sustainability.